The global nextdoor: a case study of university study away - Lee, Chance R. (Kansas State University, 2017)
Motivated by a critical theory of place, this qualitative study sought to explore the experiences of participants in a single embedded case of the Global Opportunities office at Susquehanna University. Through in-depth interviews, document analysis, and participant observation, a thorough exploration of the case was completed over a two year period. This case study explored how 15 students, faculty, and administrators in global learning programs describe their experience across immersive locations—inclusive of locations classified as domestic and international. By using a critical case study methodological framework, this work was framed by equal access to important global learning outcomes by all students—regardless of ability to pay. Global learning programs, traditionally abroad, can be a transformational experience for students able to participate—a steady 2% of university students over the previous few decades (Twombly, Salisbury, Tumanut, & Klute, 2012). As a result, 98% of American university students are not going abroad during their undergraduate experience in an academic context, most not at all. This study explored immersive programs not traditionally thought of as cross-cultural, many considered domestic experiences. Through rigorous qualitative analysis, the data in this study resulted in three themes: i. The domestic/international distinction is insufficient. ii. Civic identity is more salient in domestic and liminal experiences. iii. Location is not enough. Curriculum is essential. Implications of this work could be of interest to students in cross-cultural programs, teaching faculty and staff, student program providers of a variety of types, and university administrators of immersive experiences. Ultimately, this study sought to explore possibilities to broaden access to global learning experiences for all students.
Keywords: Global learning; Study abroad; Study away; Immersive university program; Intercultural program; Location